Ecology and human development - Bhowmik K.L.(ed.) (New Delhi, 1988)
This book provided informative material on relationship of ecology with human development, how this relationship is exploited by a community , the interaction of ecology and human development in tribal areas of Gujarat and a Bhutan habitational alienation and cultural disorganization in tribal area of Orissa, anthrophony to systems in diverse situations in West Bengal , child killing in Pavagada, industrial ecology and cultural successions in the Indo-Gangetic Plains.
Keywords: Human ecology